Adsorption and absorption of Cu in Trichoderma atroviride - Yazdani, Mazyar; Yap, Chee Kong; Abdullah, Faridah (Universiti Putra Malaysia Press, 2010)
Conventional methods for removing heavy metals from polluted waters, using chemical precipitation, sludge separation, chemical oxidation or reduction, and ion exchange, have been uneconomical and are weak processes. An alternative technique is the use of fungi as bioremediating agents. A strain of Trichoderma atroviride, isolated from a river passing through the metal polluted Serdang industrial area, was studied for its uptake and tolerance to Cu. This study found that the uptake capacity of T. atroviride for Cu ranged from 0.77 to 11 .20 mg/g in Potato Dextrose Broth in liquid media over the Cu concentration range of 25 to 300 mgIL. The isolate showed 50.3 to 85.4% adsorption and 9.6 to 47.1% absorption. These adsorption and absorption values are comparable to any good bioremediators for Cu found in the literature. This study suggests that T. atroviride is a potential bioremediator of Cu. However, further studies are still needed to confirm its practical use as a bioremediating agent under field conditions.